Viscosity approximation method for split common null point problems between Banach spaces and Hilbert spaces (Journal of Informatics and Mathematical Sciences, 2017)
We study an iterative scheme to approximation the split common null point problems for set-valued maximal monotone operators which combine viscosity method and some fixed point technically proving method between Banach spaces and Hilbert space, without using the metric projection. We prove that strong convergence theorem. Also, we show that our result can be solves the split minimization problems.
Keywords: Iterative method; Viscosity approximation method; Fixed point problems; Split common null point problems; A zero point; Nonexpansive operator; (Metric) resolvent operator